Mise-En Scene Analysis on Divergent Movie by Veronica Roth - Delina Selfia Seilatuw; Ahmad Muhid; Didit Kurniadi (Journal of Language and Health, 2020)
This research only focuses on the problem of identifying the theory of mise-en scenes found in the Divergent movie and using the mise-en scene to explore the meaning of each scene in the movie. This study also aims to identify the theory of the mise-en scene that is seen and describe the elements of mise-en-scene to explore the meaning implicit in the Divergent movie. Divergent movies were analyzed using a data approach. The analysis was completed by referring to one object that is, analysis based on the theory of mise-en scene using elements contained in it. This research uses data collection techniques. This study uses two data sources. The first is Veronica Roth's Divergent movie as the main source. The second data source is literature review by searching, collecting, reading, and studying reference books, articles, or writings that have a relationship with this research. Based on this research, the researchers concluded that the Divergent movie contains elements of the mise-en scene of each scene in the film including, setting and property, costume, lighting, acting.